Multi-wavelength thulium-doped fiber laser operating at slope efficiency of 16.57% in linear cavity configuration - Shamsudin, H.; Latiff, A.A.; Razak, N.N.; Ahmad, Harith; Harun, Sulaiman Wadi (National Institute of Optoelectronics, 2016)
A multi-wavelength thulium doped fiber laser (TDFL) with a slope efficiency of 16.57 % is demonstrated using a linear cavity consisting of a broadband mirror and a flat-cleaved fiber end in conjunction with 1552 nm pumping. The TDFL produces eleven lines within a wavelength range from 1895 to 1907 nm with a constant spacing of 1.2 nm and signal to noise ratio of more than 27 dB. The multi-wavelength TDFL is capable of generating pulses with a repetition rate of 11.62 MHz and average output power of 93 mW at the maximum pump power of 1100 mW. The proposed multi-wavelength TDFL is suitable for a multitude of real-world applications such as range-finding, medicine and spectroscopy due to its ability to operate in the eye-safe region of 2 micron.